Elastomeric Optical Waveguides by Extrusion Printing. Issue 10 (26th April 2022) - Feng, Jun; Zheng, Yijun; Jiang, Qiyang; Włodarczyk‐Biegun, Małgorzata K.; Pearson, Samuel; del Campo, Aránzazu
Abstract: Advances in optogenetics and the increasing use of implantable devices for therapies and health monitoring are driving demand for compliant, biocompatible optical waveguides and scalable methods for their manufacture. Molding, thermal drawing, and dip‐coating are the most prevalent approaches in recent literature. Here the authors demonstrate that extrusion printing at room temperature can be used for continuous fabrication of compliant optical waveguides with polydimethylsiloxane (PDMS) core and crosslinked Pluronic F127‐diacrylate (Pluronic‐DA) cladding. The optical fibers are printed from fluid precursor inks and stabilized by physical interactions and photoinitiated crosslinking in the Pluronic‐DA. The printed fibers show optical loss values of 0.13–0.34 dB cm –1 in air and tissue within the wavelength range of 405–520 nm. The fibers have a Young's Modulus (Pluronic cladding) of 150 kPa and can be stretched to more than 5 times their length. The optical loss of the fibers shows little variation with extension. This work demonstrates how printing can simplify the fabrication of compliant and stretchable devices from materials approved for clinical use. These can be of interest for optogenetic or photopharmacology applications in extensible tissues, like muscles or heart. Abstract : This work demonstrates that extrusion printing at room temperature can be used for continuous fabrication of compliant and stretchable optical waveguides with polydimethylsiloxane (PDMS) core and crosslinked Pluronic F127‐diacrylate (Pluronic‐DA) cladding, which can be employed to guide light with different wavelengths across ex vivo tissue and remotely trigger cell migration within a 3D cell culture.